Chłopaki nie płaczą? - Przystolik, Adam (Er(r)go. Teoria - Literatura - Kultura, 2003)
Adam Przystolik's review of "Boys Don't Cry? Rethinking Narratives of Masculinity and Emotion in the US," edited by Milette Shamir and Jennifer Travis (2002).